The edge of the earth [large type] : a novel - Schwarz, Christina (Wheeler Publishing, 2013)
Trudy is a polished, educated young woman from a respectable upper-middle-class family, and it's assumed she'll marry the son of her parents' closest friends. Yet Trudy is restless for more stimulation than 1897 Milwaukee allows. When she falls in love with enigmatic and ambitious Oskar, Trudy believes she's found her escape. The couple leaves for a job at a remote California lighthouse, where it turns out there is more going on than Trudy could ever have imagined.